Hospitalizations due to heart failure: major differences between East and West Germany even 30 years after reunification. (25th November 2020) - Dorr, M; Riemer, U; Christ, M; Stoerk, S; Wachter, R
Abstract: Background: Heart failure (HF) is one of the most common diseases in the adult population with a prevalence of about 4% and a steady increase due to demographic and medical developments. In Germany, it is the most common primary diagnosis for inpatient treatment. Little was known so far about regional differences. Methods: We retrospectively analyzed aggregated administrative data on the number and characteristics of in-patients in Germany for the period 2000 to 2017, obtained from the German Federal Health Monitoring, an annual complete census of in-patient routine data. The number and duration of hospitalizations as well as hospital mortality with the main diagnosis "I50" (HF) were analyzed over time with a special emphasis on regional differences between the federal states. Results: The number of HF-related hospitalizations in Germany increased continuously: from 239, 694 in 2000 to 464, 724 cases in 2017 (+94%). This increase was more pronounced in East Germany than in West Germany (119% vs. 88%) [Figure 1]. The proportion of HF-related hospitalizations in relation to the total number of hospitalizations rose from 1.4% to 2.3% (relative increase +67%) in whole Germany. Accordingly, HF was the most frequent disease-related reason for hospitalizations in Germany in 2017, again with marked differences between East and West Germany (relative increase +96% vs. +61%). Similar differences were found after age-standardization: hospitalization rate due to HF in 2017 was higher in the East than in West Germany (609 vs. 490 cases per 100, 000 population), reflecting a major increase compared to year 2000 (49% vs. 36%). Despite a continuous decrease in the length of stay (from 14.3 to 10.2 days; –29%), the total number of HF-related hospital days in Germany increased by 38% (4.72 million hospital days in 2017). In East Germany, the number of hospital days increased by 51%, in West Germany by 35% [Figure 1]. The in-hospital mortality rate of HF patients remained unchanged between 2000 and 2017 at about 38, 000 cases per year, corresponding to 8.2% in 2017 (East Germany 8.4%, West Germany 8.2%). With a contribution of 8.9% of all hospital deaths, HF constituted the leading cause in 2017. Again, this proportion was higher in East compared to West Germany throughout the entire observation period (2017 10.8% vs. 8.5%). The rate of HF-related in-hospital deaths was also higher in East than in West Germany (2017: 65 vs. 43 per 100, 000 population) [Figure 1]. Conclusion: HF continues to be the most common cause of hospitalization and hospital deaths in Germany. HF-related morbidity and mortality parameters are higher in East than in West Germany. Possible explanations for this finding are differences in the prevalence of risk factors and the structure of patient care between these regions. A more detailed understanding of these striking discrepancies 30 years after the German reunification requires further investigations. Funding Acknowledgement: Type of funding source: None